Synanthropy of Calliphoridae and Sarcophagidae (Diptera) in Bogotá, Colombia (2012)
Calliphoridae and Sarcophagidae have medical and forensic importance. Species of these families are the first insects colonizing corpses and are, therefore, useful in establishing postmortem interval and as indicators in corpse transfer. The synanthropic index (SI) measures the relation of dipteran species with human settlements. Our main objective was to determine the synanthropic index of these families during the rainy and dry seasons in Bogotá. Captures were carried out using traps with baits (beef liver) in three zones (urban, rural, and forest areas). In the family Calliphoridae, the most abundant species were Calliphora vicina (Robineau-Desvoidy) with a sinanthropy index (SI) of +83. 1, followed by Lucilia sericata (Meigen) (SI = +92. 2) and Compsomyiops verena (Walker) (SI = +42. 0). Calliphora nigribasis (Macquart) was not associated with human settlements, while Sarconesiopsis magellanica (Le Guillou) was present in the three zones and considered hemisynanthropic (SI = +19. 0). Roraimomusca roraima (Townsend) was reported for the first time in Bogotá and was a non-synanthropic species (SI = -36. 0). On the other hand, in Sarcophagidae, three species were collected: Ravinia rufipes (Twonsend), Ravinia colombiana (Lopes), and Boettcheria sp1, which were abundant in the rural and forest zones, the first having a dual characterization as synanthropic and hemisynanthropic, while the other two were hemisynanthropic. Our data showed differences in the association of Calliphoridae species with the three environments, whereas Sarcophagidae were distributed in locations with a lower human impact. © 2012 Sociedade Entomológica do Brasil.